Collagen I Induces Preeclampsia-Like Symptoms by Suppressing Proliferation and Invasion of Trophoblasts - Feng, Yinglin; Chen, Xia; Wang, Huiqiao; Chen, Xueping; Lan, Zixin; Li, Pan; Cao, Yingshi; Liu, Mian; Lv, Jin; Chen, Yun; Wang, Yu; Sheng, Chao; et al. (Frontiers in Endocrinology, 2021)
Preeclampsia is a common obstetric disorder affecting 2-8% of pregnancy worldwide. Fibrosis is an important histological change occurring in preeclamptic placenta, and might depend on the excess deposition of collagen I. However, the role of fibrotic placenta and collagen I in the pathogenesis of preeclampsia remains unclear. Therefore, we analyzed the collagen deposition and the expression of Collagen I in human placenta by Masson staining, Sirius red staining and western blotting. Further, the role of collagen I in preeclampsia pathogenesis was studied in C57BL/6 mice. HTR-8/SVneo cells were used to investigate the mechanisms underlying the effects of collagen I in trophoblasts by transcriptome sequencing and pharmacological agonists. Human preeclamptic placenta exhibited a significantly higher degree of fibrosis in stem villi and terminal villi than normal placenta, and was characterized by collagen I deposition. In vivo, a single injection of collagen I on gestational day 0.5 led to an increase in systolic pressure of pregnant mice from gestational days 4.5–17.5, to a decrease in weight and number of embryos, and to enhanced placental collagen I expression and degree of fibrosis compared with control mice. In vitro, collagen I attenuated the proliferation and invasion of HTR-8SV/neo cells. This effect could be reversed by treatment with agonists of ERK and β-catenin. Moreover, transcriptome sequencing demonstrated that signaling pathways related to cell proliferation and invasion were significantly downregulated in HTR-8SV/neo cells. Thus, we propose that collagen I induced preeclampsia-like symptoms by suppressing the proliferation and invasion of trophoblasts through inhibition of the ERK phosphorylation and WNT/β-catenin signaling pathways. Our findings could pave the way to the discovery of small-molecule inhibitors for preeclampsia treatment and future studies with larger sample size are required.